Sustainable activities in manufacturing enterprises: Consumers’ expectations - Patrícia Jánošová (Ural State University of Economics, 2021)
Generating profit is one of the primary reasons behind the establishment and functioning of any enterprise that predetermines its behavior, inter alia, in the context of sustainability. Manufacturing enterprises are a specific area in terms of sustainability, as they have a great impact on social and environmental indicators. The paper analyses the issues of sustainable production in the Slovak Republic. The methodological basis of the study is the triple-bottom line concept. The methods used in the paper are analysis, synthesis and comparison. Within the framework of the research, the author has conducted two surveys in the form of open-ended questions. The first part is dedicated to consumers’ evaluation of the production activity of manufacturing enterprises. Consumers as stakeholders of an enterprise have a significant influence on its activities due to the fact that they create market demand. The survey results show that the main methods for stimulating consumers’ sustainable behaviour are the use of compostable packaging and abandoning chemical sprays. The second part is an overview of barriers and problems at enterprises that prevent consumers in the Slovak Republic from transitioning to a sustainable lifestyle. Among them are excessive plastic packaging and high prices for eco-products. The presented activities determine the direction for managers how to lead enterprises to sustainability in the market. The most significant findings from the surveys point to the excessive and reckless use of plastic by manufacturing enterprises. Consumers demand that managers make rational decisions about the origin, quantity and quality of materials used in production, including the long-term consequences and environmental impact of materials.